PENGARUH DESAIN PRODUK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI PT. CAPELLA DYNAMIC NUSANTARA NAGOYA BATAM - Hari Yusnan Affandi; Dini Anggraini (LPPM Universitas Ibnu Sina, 2021)
Age has made motorbikes as a necessary means of transportation. The purpose of this study was to determine the effect of product design, product quality and price on purchasing decisions. The population of this research is the consumers of PT. Capella Dynamic Nusantara Nagoya Batam, totaling 255 people. The sample consisted of 72 respondents, who were taken by random sampling method. Data analysis using multiple regression and hypothesis testing and using SPSS version 23. The results of this study concluded that product design has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, prices have a significant effect on purchasing decisions. Product design, product quality and price simultaneously have a significant effect on purchasing decisions